Analisis Fungsi dan Estetika Logo ‘Nyenyes’ Palembang - Patriansah, Mukhsin; Viatra, Aji Windu; Yazid, Iqbal Maulana (Lembaga penelitian dan pengabdian kepada Masyarakat, 2025)
A logo as a visual identity contains design elements as symbols to represent the values, goals and characteristics of the entity being represented. The thing behind the interest of the author of this research is the use of the word